The role of infectious agents in urogenital cancers - Alibek, Kenneth; Karatayeva, Nargis; Bekniyazov, Ildar (BioMed Central, 2012)
Since the late 1990s, infectious agents have been thought to play a role in the pathogenesis of approximately 15% of cancers. It is now widely accepted that infection of stomach tissue with the bacteria Helicobacter pylori is an important cause of stomach adenocarcinoma. In addition, oncogenic viruses, such as papilloma viruses, herpes viruses, and hepadnaviruses are strongly associated with increased risk of cervical cancer, lymphomas, liver cancer, amongst others. However, in the scientific community the percentage of cancers caused by pathogens is believed to be far higher than 15%. A significant volume of data collected to date show an association between infectious agents and urogenital cancers. These agents include Chlamydia trachomatis, Neisseria gonorrhoea, Mycoplasma genitalium and certain viruses that have been implicated in ovarian cancer.
Keywords: urogenital cancers; ovarian cancer; cervical cancer; Bladder cancer; Kidney cancer; Chlamydia trachomatis; Neisseria gonorrhea; Mycoplasma genitalium; Schistosoma haematobium; HPV; Epstein-Barr; CMV; Human polyomaviruses; Research Subject Categories::MEDICINE::Microbiology, immunology, infectious diseases